The Influence of Sowing Date and Seeding Density on the Yield of Soybean Glycine max (L.) Merrill - Elżbieta Radzka; Katarzyna Rymuza; Paweł Cała (Agriculture)
The current study aimed to determine the optimum agronomic conditions—specifically sowing date and seeding density—for soybean cultivation in a temperate climate. A field experiment was conducted to evaluate three sowing dates based on soil temperature (S1—9 °C, S2—12 °C, S3—15 °C) and three seeding densities (D1—50, D2—70, D3—90 seeds·m−2). A field experiment was conducted in the years 2017–2019 in eastern Poland (Central Europe). Yields were strongly influenced by weather conditions. In 2019, the average yield was 2.61 Mg·ha−1, making it the most favorable year, whereas 2018 was the least favorable, with an average yield of 1.41 Mg·ha−1. Seeding density also affected soybean yields—the highest yield was obtained at the medium density (D2—2.36 Mg∙ha−1). On the other hand, the highest thousand seed weight (159.30 g·m−2) was achieved at the lowest density (D1). Plant height and pod length depended on the sowing date. The tallest plants (69.96 cm) and the longest pods (4.55 cm) were obtained with early sowing (S1). The number of seeds per pod ranged from 1.8 to 2.7, with the highest values recorded in 2017, mainly with early sowing (S1) and low density (D1). It is recommended that sowing strategies be flexibly adjusted to the meteorological conditions of a given season. The findings indicate that appropriate selection of sowing parameters can significantly enhance the efficiency and stability of soybean yields under the variable climatic conditions of Poland.